An overview of unsolved deficiencies of direct methanol fuel cell technology: factors and parameters affecting its widespread use. (18th February 2014) - Kumar, Piyush; Dutta, Kingshuk; Das, Suparna; Kundu, Patit Paban
SUMMARY Direct methanol fuel cells (DMFCs) have evolved over the years as a potential candidate for application as a power source in portable electronic devices and in transportation sectors. They have certain associated advantages, including high energy and power densities, ease of fuel storage and handling, ability to be fabricated with small size, minimum emission of pollutants, low cost, ready availability of fuel and solubility of fuel in aqueous electrolytes. However, in spite of several years of active research involved in the development of DMFC technology, their chemical‐to‐electrical energy conversion efficiencies are still lower compared with other alternative power sources traditionally used. This review paper will focus on the existing issues associated with DMFC technology and will also suggest on the possible developmental necessities required for this technology to realize its practical potentials. Copyright © 2014 John Wiley & Sons, Ltd.